The Influence of Physical Work Environment and Organizational Culture on Employee Work Productivity at PT. PLN (Persero) UID Sulselrabar - Risma, Risma; Haeruddin, M. Ikhwan Maulana; Hasbiah, Siti; Kurniawan, Agung Widhi; Abadi, Rahmat Riwayat (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the physical work environment and organizational culture on employee productivity at PT. PLN (Persero) UID Sulselrabar. The study uses a quantitative method with an associative process. Data was collected through observation, interviews, questionnaires, and literature review. The population in this study consisted of all employees at PT. PLN (Persero) UID Sulselrabar, with a sample size of 116 individuals, using stratified random sampling as the sampling technique. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS). The research results indicate that the Physical Work Environment has a positive and significant effect on Work Productivity, meaning that the better the work environment, the higher the employees' work productivity will be. Organizational Culture also has a positive and significant effect on Work Productivity, meaning that the better the organizational culture, the higher the employees' work productivity will be as well. Additionally, the Physical Work Environment and Organizational Culture simultaneously have a significant impact on Work Productivity, meaning that the physical work environment and organizational culture together influence the work productivity of employees at PT PLN (Persero) UID Sulselrabar.